Imaging of Soft Tissue Tumors - de Schepper, Arthur M.; de Schepper, Arthur M. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
This richly illustrated book provides a comprehensive survey of the growing role of medical imaging studies in the detection, staging, grading, tissue characterization, and post-treatment follow-up of soft tissue tumors. For each tumor group, imaging findings are correlated with clinical, epidemiologic, and histologic data. The relative merits and indications of various imaging modalities are discussed and compared. Particular emphasis is placed on MRI because of its unique contrast resolution and multiplanar imaging capabilities. This third, revised and updated edition includes new chapters on genetics and molecular biology and on pathology of soft tissue tumors, with respect to the new World Health Organization (WHO) calssification of soft tissue tumors. It aims to serve both as a systematic, descriptive textbook and as a rich pictorial database of soft tissue masses. The addition of numerous new illustrations of common and rare soft tissue tumors, will further increase the scientific and educational value of this third edition. This clinically oriented book will be of use not only to radiologists but also to orthopedic surgeons, oncologists and pathologists.